In-situ organic-inorganic ferroelectric layer growth for efficient perovskite solar cells with high photovoltage. (March 2023) - Xiao, Lingbo; Xu, Xiaoli; Lu, Zheng; Zhao, Jie; Liu, Ruiyuan; Ye, Yaqi; Tang, Rujun; Liao, Wei-Qiang; Xiong, Ren-Gen; Zou, Guifu
Abstract: Halide perovskite solar cells (PSCs) have shown outstanding performance, which can be further improved through enhancing the built-in electric field ( V bi ) and reducing non-radiative recombination pathways. Here we in-situ grow an organic-inorganic ferroelectric layer on the perovskite film, which can be easily and quickly processed even at room-temperature within one minute. The in-situ process endows intimate growth of ferroelectric layer on the original perovskite grains, which can reduce the formation of grain boundaries and thus minimize the recombination of electron and hole at grain boundaries. The V bi of the PSCs is enhanced from 1.02 V to 1.28 V due to the widened space charge depletion region after the formation of ferroelectric layer. Finally, an output photovoltage up to 1198 mV is achieved with a champion efficiency of 22.45% and a low voltage deficit of 352 mV. The strategy offers a new platform of growing intimate ferroelectric layers on perovskite photoactive films for integration between ferroelectrics and PSCs. Graphical Abstract: ga1 Highlights: An organic-inorganic ferroelectric layer is in-situ grown on the perovskite active film. The in-situ process endows partial epitaxial growth of ferroelectric layer on the original perovskite grains. The built-in electric field of perovskite solar cell device is enhanced from 1.02 V to 1.28 V. The photovoltage up to 1198 mV with a low voltage deficit of 352 mV is achieved.